2014 IEEE International Solid-State Circuits Conference Digest of Technical Papers (ISSCC) 2014
DOI: 10.1109/isscc.2014.6757411
|View full text |Cite
|
Sign up to set email alerts
|

12.9 A 1.55&#x00D7;0.85mm<sup>2</sup> 3ppm 1.0&#x03BC;A 32.768kHz MEMS-based oscillator

Abstract: Mobile time-keeping applications require small form-factor, tight frequency stability, and micro-power 32.768kHz clock references. Today's 32kHz quartz resonators and oscillators are facing challenges in size reduction [1,2]. Previously described MEMS-based oscillators can achieve tight accuracy but operate at high frequency with power unsuitable for mobile applications [3]. This paper introduces a 32kHz MEMS-based oscillator. Based on a comparison table of recent oscillators shown in Fig. 12.9.6, it offers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It was demonstrated that frequency accuracy at the ppm level and temperature stability can be achieved with frequency synthesizer techniques, the drawback of which is the relatively high power. The power of the frequency synthesized MEMS oscillator is approximately 10 times larger than those of quartz crystal oscillators of the same level owing to the increased powers of the phase-locked loop (PLL) circuits, and limits its applications [6][7][8][9][10][11][12]. Low-power techniques are required for both frequency tuning and temperature stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that frequency accuracy at the ppm level and temperature stability can be achieved with frequency synthesizer techniques, the drawback of which is the relatively high power. The power of the frequency synthesized MEMS oscillator is approximately 10 times larger than those of quartz crystal oscillators of the same level owing to the increased powers of the phase-locked loop (PLL) circuits, and limits its applications [6][7][8][9][10][11][12]. Low-power techniques are required for both frequency tuning and temperature stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the discrete nature of these off-chip micromechanical resonators still impedes the system miniaturization and circuit integration for future multiband, multimode wireless transceivers [9], vibrational inertial sensors [10], and timing references [11], [12]. To realize MEMS resonators monolithically integrated with circuitry, in recent years CMOS-MEMS resonator platforms based on a foundryoriented 0.35 μm 2-poly-4-metal (2P4M) CMOS technology [13]- [15] and 0.18 μm 1-poly-6-metal (1P6M) CMOS process [16], [17] have been developed to fabricate integrated vibrating micromechanical structures side by side with circuits.…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes the smallest production 32kHz XO and TCXO [14]. The XO combines a temperature stable MEMS resonator with sustaining amplifier and fractional-N PLL to calibrate the output frequency over production tolerances, when configured and calibrated as a TCXO, a temperature-to-digital converter (TDC) adjusts the frac-N to compensate frequency over temperature.…”
mentioning
confidence: 99%